The evaluation and management of patients with LDL-C ≥ 190 ​mg/dL in a large health care system - Candace L. Jackson; Zahid Ahmad; Sandeep R. Das; Amit Khera (Elsevier, 2020)
Objectives: Patients with severe hyperlipidemia (low-density lipoprotein-cholesterol (LDL-C) ≥190 ​mg/dL) have a significantly increased risk of cardiovascular disease (CVD) and are more likely to have familial hypercholesterolemia (FH). We sought to determine how often health care providers recognize the implications of and adjust therapy for an LDL-C ≥190 ​mg/dL. Methods: We conducted a retrospective review of patients with an LDL-C measurement in the medical record of a large health care system between November 2015 and June 2016. Patients were restricted to those with LDL-C ≥190 ​mg/dL and without secondary causes of dyslipidemia, with sensitivity analyses for those with LDL-C ≥220 ​mg/dL. Results: Of 27,963 patients, 227 had LDL-C ≥190 ​mg/dL. Only 21% were on a statin at the time of LDL-C measurement. More than 90% had a follow-up clinic visit, but 41% had no change in treatment. FH was only included in the differential for 14%. The presence/absence of a family history of dyslipidemia, myocardial infarction, and premature CVD were documented in 26%, 29%, and 31%. Only 20.7% and 22.1% had documentation of the presence or absence of tendinous xanthomas or corneal arcus, respectively. Among those without prior specialist care (cardiologist or endocrinologist), only 13% were referred. These measures were only slightly better for those with LDL-C ≥220 ​mg/dL. Conclusion: In a large health care system, the possibility of FH was rarely acknowledged in those with residual LDL-C ≥190 ​mg/dL, few were referred to specialists, and therapeutic adjustments were suboptimal. Additional efforts are required to understand barriers to improving the evaluation and management of patients with LDL-C ≥190 ​mg/dL.